Drying drives decline in muskrat population in the Peace-Athabasca Delta, Canada - Ellen M Ward; Steven M Gorelick (Environmental Research Letters, 2018)
Empirical and anecdotal reports suggest that muskrat are in decline across North America, including in the Peace-Athabasca Delta (‘Delta’), Canada, one of the largest inland deltas in the world and part of a World Heritage Site with ‘in Danger’ status pending. Muskrat are a key ecological indicator in the Delta. We investigate whether the large-scale loss of critical habitat over the past half-century could be driving a decline in muskrat abundance in the Delta. To do this, we use the Landsat record (1972–2017) to construct a 46 year record of inundation, and compare changes in the extent of critical habitat to the survey record for muskrat (1970–2016) over this 5500 km ^2 region. Results show that the declines in critical habitat and muskrat numbers in the Delta are synchronous: ∼1450 km ^2 of temporarily inundated regions that support critical habitat have diminished by ∼10 km ^2 yr ^−1 over the past 46 years, while the muskrat population density (houses/km ^2 ) has also declined and is significantly related to critical habitat area (km ^2 ) ( R ^2  = 0.60, P  = 0.0001). These findings have implications for the Delta, a Ramsar Wetland of International Importance in part for its role as a habitat for nearly 200 species of birds, many of which rely on the aquatic habitat considered here. Our results further suggest that the loss of wetland habitat is a primary driver of the decline of muskrat across the species’ native range.